MEASURES OF ELIMINATION OF SALMONELOSIS OF BROILERS IN A PRIVATE HOUSEHOLD - Peredera, O. O.; Peredera, R. V. (Scientific Progress & Innovations, 2022)
Salmonellosis is an extremely common disease in many animals and birds. This disease is especially dangerous for young birds because it affects both productive poultry ‒ chickens, turkeys, ducks, pheasants, guinea fowl, quails, and synanthropic - sparrows, pigeons, starlings and more. The disease causes great damage to poultry farms of various forms of ownership and capacities, which is associated with losses due to product shortages and high mortality among sick young animals. Therefore, the development of various treatment regimens for poultry, including young broilers, is currently relevant, including the use of publicly available drugs. The aim of the work was to develop an effective treatment regimen for salmonellosis in broilers in private farms. In order to determine the effectiveness of various treatment regimens in the conditions of suspected salmonellosis on a private farm where broilers were bred, a comprehensive diagnosis was made with confirmation of the diagnosis of salmonellosis by bacteriological examination of pathological material and susceptibility to antibacterial agents. Subsequently, two treatment regimens were tested on two groups of sick young broilers, 20 heads each. In the first group, the drug Questigin (manufacturer KRKA, Slovenia) was used for therapeutic purposes, which was diluted with water and fed to sick birds. The second used a suspension of Amoxicillin (manufactured by Pharmaton, Ukraine), which was administered by intramuscular injection. Both experimental groups of birds used the probiotic supplement Bioferm (Bioferm, Ukraine) to support the digestive tract and strengthen the body's overall resistance. The most effective regimen was found to be the use of Amoxicillin as a suspension for injection, which was injected into the pectoral muscle for three consecutive days at a dose of 15 mg per 1 kg of body weight in combination with the probiotic Bioferm. In particular, improvement of the clinical condition of sick young animals was registered from 4‒7 hours after drug administration. Instead, when using the Questigin treatment regimen in combination with the Bioferm probiotic, the general condition improved 6–18 hours later. The positive effect of treatment in the second experimental group was also confirmed by the number of birds that recovered, in total it was 18 heads and was 20 % higher than the bird in the first experimental group. Disinfection of the environment, premises where the bird was kept, was carried out with 1.5 % solution of Brovadez-plus (manufacturer Brovapharma, Ukraine) by fine spraying and surface treatment with a sponge soaked in the working solution.